To Impute or Not to Impute? A Review of Alternative Poverty Estimation Methods in the Context of Unavailable Consumption Data - Hai-Anh H. Dang (Global Labor Organization (GLO), 2018)
There is an increasingly stronger demand for more frequent and accurate poverty estimates, despite the oftentimes unavailable household consumption data. We offer a review of alternative imputation methods that have been employed to provide poverty estimates in such contexts. These range from estimates on a nonmonetary basis, estimates for specific project targeting or tracking trends at the national level, to estimates at a more disaggregated level, as well as estimates of poverty dynamics. We provide a concise and accessible synthesis, which serves as an introduction to the literature. Our focus is on intuition and practical insights that highlight the nuanced differences between the existing methods rather than technical aspects.
Keywords: C15; I32; O15; 330; poverty; imputation; consumption; wealth index; synthetic panels; household survey